SOSIALISASI DAN EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA UPT SDN 066050 MEDAN DENAISOSIALISASI DAN EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA UPT SDN 066050 MEDAN DENAI - Delisma Simorangkir; Zuliawati Zuliawati (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
This article is an analysis of the healthy lifestyle especially among the students of UPT SDN 066050 Medan Denai. A healthy lifestyle is an important thing that should be fulfilled by every society but the society pays less attention to what the times of every society struggle to survive or work. Victims of worm disease Worms which are parasitic animals not only take nutrients from the intestines but also damage the walls of the intestines disrupting the absorption of these nutrients. PKM activities are carried out in three phases namely the production implementation phase and the evaluation phase and the reporting phase. PKM activities are useful for increasing health knowledge and standards where students can participate in educating friends and family about health and practicing a healthy lifestyle in choosing good food for health How to wash hands properly correct and correct and the benefits and importance of getting in shape once in a 6 month time.